Racial and ethnic differences in the relationship between infant loss after prior live birth and hypertensive disorders in pregnancy. (12th December 2022) - Wagstaff, Kathryn; Williams, Joni S.; Garacci, Emma; Shour, Abdul R.; Palatnik, Anna; Egede, Leonard E.
Abstract: Background: Race and ethnicity influence the distribution and severity of hypertensive disorders of pregnancy (HDP) in the U.S. population, although the impact of prior infant loss on this relationship requires further investigation. Objectives: The aim of this study was to assess the relationship between history of infant loss and the risk of HDP by maternal race and ethnicity. Methods: For this large cross-sectional study, data were analyzed from the National Center for Health Statistics Vital Statistics Natality Birth Data, 2014–2017. The primary outcome was HDP, and the primary predictor was infant loss after prior live birth. Maternal race/ethnicity was the secondary predictor categorized as Non-Hispanic White (NHW), Non-Hispanic Black (NHB), Hispanic, Asian, or Other. Multiple logistic regression was used to assess the association between history of infant loss and HDP by race and ethnicity. Results: The 9, 439, 520 women included in this sample were 51% NHW, 15% NHB, 25% Hispanic, 6% Asian, and 3% Other with a mean age of 29.8 ± 5.3 years. In adjusted analyses, infant loss after prior live birth was significantly associated with an 11% odds of HDP (OR 1.11, 95% CI 1.08, 1.13). Stratified by race, NHB (OR 1.28; 95% CI 1.21, 1.36) women had significantly higher odds of HDP, and Hispanic (OR 0.84, 95% CI 0.79, 0.90) and Asian (OR 0.85, 95% CI 0.75, 0.97) women had significantly lower odds compared to NHW women. Within races, all women with infant loss after prior live birth had significantly higher odds of HDP ( p < .001), except Other women ( p = .632). Conclusions: Infant loss after prior live birth was significantly associated with higher odds of HDP among NHB women after adjusting for covariates. Further research is warranted to assess underlying mechanisms associated with higher odds of HDP in NHB women.